The level of tertiarisation of European Union countries and regions - Смаль, Валентина (Human Geography Journal, 2014)
Tertiarisation of economy is an important feature of the postindustrial development. The paper presents results of the research devoted to determining the level of development of tertiary sector in European Union countries and their regions. Main general and specific trends of service sector development in countries with different level of market economy maturity are revealed on the base of analysis of some separate indices and calculated integral coefficient of tertiarisation.